2020
DOI: 10.2147/copd.s254477
|View full text |Cite
|
Sign up to set email alerts
|

<p>Promoting Community Pharmacy Practice for Chronic Obstructive Pulmonary Disease (COPD) Management: A Systematic Review and Logic Model</p>

Abstract: This study aimed 1) to identify and analyse the professional services provided by community pharmacists for chronic obstructive pulmonary disease (COPD) management; and 2) to develop a logic model for community pharmacy practice for COPD management. Methods: A systematic review with a logic model was applied. English-language databases (PubMed, Web of Science, Embase, and Scopus) and a Chinese database (CNKI) were searched for articles published between January 2009 and June 2019. Studies concerning pharmacist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(283 reference statements)
0
6
0
Order By: Relevance
“…The community pharmacy is easily accessible and perceived to be affordable by the public, making it often the first point of contact in the healthcare system [44,45]. The role of the pharmacist has evolved beyond mere medication adjustments and now encompasses a diverse range of patient-centred health management tasks [45].…”
Section: Role Of the Community Pharmacy In The Epoc Patients' Continu...mentioning
confidence: 99%
“…The community pharmacy is easily accessible and perceived to be affordable by the public, making it often the first point of contact in the healthcare system [44,45]. The role of the pharmacist has evolved beyond mere medication adjustments and now encompasses a diverse range of patient-centred health management tasks [45].…”
Section: Role Of the Community Pharmacy In The Epoc Patients' Continu...mentioning
confidence: 99%
“…[15][16][17][18] Former studies showed that community pharmacies are well-equipped to deliver educational services to patients with asthma, 19 and to patients with COPD. 20 For the pharmacy team to optimally provide these services, trust is paramount. Also because high trust is associated with improving patients' medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…20 Despite the emerging evidence for the benefits of improved patient outcomes associated with hospital pharmacist intervention, much of the current literature designates a prime focus on the role of pharmacist at the community level for COPD management. 21,22 Indeed, within the scope of COPD, the disease is deemed preventable should risk factors such as tobacco smoking and air pollution can be avoided, while under-diagnosis and mis-diagnosis are often common, which are areas best addressed at the community setting. 23 Nevertheless, COPD patients also receive care in the hospitals during specialist consultation, ICU admission and hospitalization.…”
Section: Introductionmentioning
confidence: 99%